SWOT ANALYSIS IMPLEMENTATION IN INCREASING ARGO CHERIBON TRAIN TICKET MARKETING STRATEGY - Handoko Handoko; Fahruli Irawan (CV. Syntax Corporation Indonesia, 2023)
By using SWOT this study aims to find out the state of the company, find out the factors in improving train ticket marketing and look for efforts to improve train ticket marketing based on the factors that have been obtained in the research. Data collection was obtained using interviews and questionnaires for data processing using qualitative descriptive analysis methods. To find out the internal factors of the company comes from the 4P marketing mix and for external factors the company comes from the environment, social and technology. After obtaining the factors, a SWOT analysis and weighting and rating were carried out using the IFAS and EFAS methods. In determining informants and research samples using the Purposive Sampling method. The informant in this study was an employee of the DAOP 3 Cirebon passenger transportation unit who was responsible for the marketing of train tickets. Based on the calculation of IFAS and EFAS, the value of Strength 2.28 and weakness of 0.67 is obtained so that the difference in value is obtained by 1.61, while for the difference between the value of opportunity and threat is 0.35 So that it forms coordinates (1.61,0.35). The results of the SWOT analysis found that the company's position is in quadrant 1 so that the strategy applied is an aggressive strategy where the best possible utilize strengths and opportunities such as maintaining service quality, providing promos and promoting customers to introduce their products